2011
DOI: 10.1159/000322919
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control for Intravascular Intrauterine Transfusion Using Cumulative Sum (CUSUM) Analysis for the Monitoring of Individual Performance

Abstract: Introduction: Intravascular intrauterine transfusion (IUT) is an effective and relatively safe method for the treatment of fetal anemia. Although implemented in centers all over the world in the 1980s, the length and strength of the learning curve for this procedure has never been studied. Cumulative sum (CUSUM) analysis has been increasingly used as a graphical and statistical tool for quality control and learning curve assessment in clinical medicine. We aimed to test the feasibility of CUSUM analysis for qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…A more advanced gestational age at birth in later years of the study and/or advancements in prenatal and especially neonatal management in the past decades may have contributed, as well as a decrease in IUT complications . Centralization of fetal therapy and neonatal care in large volume centers is increasingly important for quality of care …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more advanced gestational age at birth in later years of the study and/or advancements in prenatal and especially neonatal management in the past decades may have contributed, as well as a decrease in IUT complications . Centralization of fetal therapy and neonatal care in large volume centers is increasingly important for quality of care …”
Section: Discussionmentioning
confidence: 99%
“…6 Centralization of fetal therapy and neonatal care in large volume centers is increasingly important for quality of care. 30 Infants born alive after treatment with IUT(s) seem to be in better neonatal condition nowadays, being less anemic at birth (despite longer intervals between the last transfusion and birth) and needing less exchange transfusions. We found that both additional intraperitoneal transfusion, in adjunct to intravascular transfusion, and more advanced gestational age at birth were independently associated with higher neonatal hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Refraining from fetal paralysis, arterial and free loop needling were found to be important risk factors for adverse outcome [29]. Furthermore, operators should perform at least 10 IUTs per year to retain their competence [67].…”
Section: (Procedure-related) Complicationsmentioning
confidence: 99%
“…In the literature, procedure-related fetal loss ranges from 0.9 to 4.9% per procedure [7,50,51,52,53,54] and was found to be associated with fetal hydrops [54,55], early gestational age [50,51], failing to use fetal paralysis during IUT [7], transfusion at a free loop of cord or arterial puncture [7,52], experience of the operator [52,56] and severity of fetal anemia [53]. Interestingly, preterm premature rupture of membranes after transfusion appears extremely rare, e.g.…”
Section: Associated Risks Of Iutmentioning
confidence: 99%